1991
DOI: 10.1007/bf00304496
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dsDNA: choice of assay in relation to clinical value

Abstract: Antibodies to DNA are quite specific for systemic lupus erythematosus (SLE) and occur in the majority of SLE patients. Therefore, their detection is an important diagnostic aid to the clinician. Detection of anti-dsDNA may precede the diagnosis of SLE by more than a year. Fluctuations in the level of anti-dsDNA in an individual patient may give important information on the clinical status of the patient. Four of the most important methods developed for the measurement of anti-dsDNA antibodies will be discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 53 publications
1
36
0
1
Order By: Relevance
“…One study on 440 mixed SLE patients reported the sensitivity of the Farr assay at 95 and 99% SICC to be 72 and 56%, respectively (19), which is similar to our 76 and 57% and to the results from other previous studies (3). By combining the results for specimens identified as positive by the EL-ssDNA and EL-dsDNA at 99% SOCC with results from EL-dsDNA at the 95% SICC, three categories of specimens emerged: those very likely to have SLE (78%), likely to have SLE, but in need of confirmation by either Farr or CL-IFA (11%), and normal by any method (11%; Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One study on 440 mixed SLE patients reported the sensitivity of the Farr assay at 95 and 99% SICC to be 72 and 56%, respectively (19), which is similar to our 76 and 57% and to the results from other previous studies (3). By combining the results for specimens identified as positive by the EL-ssDNA and EL-dsDNA at 99% SOCC with results from EL-dsDNA at the 95% SICC, three categories of specimens emerged: those very likely to have SLE (78%), likely to have SLE, but in need of confirmation by either Farr or CL-IFA (11%), and normal by any method (11%; Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Second, the Farr radioimmunoassay is often the standard by which all other methods of anti-dsDNA antibodies detection in SLE are judged (2). Farr is quantitative, with results that can be expressed in IU/ml, measures high avidity antibodies, and is considered specific for SLE when high quality, radiolabeled, procariotic DNA is used (2)(3)(4). It has its drawbacks (5): cannot be automated and is the most labor intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Because ds-DNA-Ab may occur in a wide spectrum of diseases and even in healthy volunteers, diagnostic tests must be highly specific. The Farr RIA is assumed to meet this need best (4,5 ). To improve the diagnostic accuracy of ds-DNA-Ab tests, new tests have been developed, including ELISAs with different preparations of ds-DNA antigens as well as an automated enzyme fluoroimmunoassay using plasmid DNA as antigen.…”
mentioning
confidence: 99%
“…Cytologic examination of peritoneal fluids forms part of the staging process for ovarian cancer and influences therapeutic interventions (3 ). It is known that regardless of International Federation of Gynecology and Obstetrics (FIGO) stage, positive peritoneal washing cytology predicts poor prognosis for women with epithelial tumors of the genital tract, except for patients with borderline ovarian tumors (4 ). Because of the diagnostic pitfalls entailed in the cytologic examination of peritoneal washings (5 ), some additional methods for peritoneal fluid diagnosis have been tested, including flow cytometric DNA analysis (6 ) and a telomerase assay (7,8 ).…”
mentioning
confidence: 99%
“…Of these, the Farr assay is regarded as the most specific since it detects only antibodies with a relatively high avidity for dsDNA [14]. Recently, we demonstrated that Farr positivity can also be the result of binding of complexes composed of nucleosomal material and anti-nucleosome antibodies [15].…”
Section: Introductionmentioning
confidence: 98%